The Effect Of The Imposition Of Tax Tax On Land And Building Rights (BPHTB) On The Application For New Certificate On Land And Building In Cijambe Village, Sumebang Regency - Vira Febia Tunisia; Lina Lisnawati; Sofia Anisa (LPPM Universitas Sebelas April, 2019)
Inventory of goods is the most active asset in the operations of trading and manufacturing companies. The effect of inventory on profit is more easily seen when business activities are fluctuating. so that a tool is needed to monitor the inventory so that internal inventory control is achieved, namely, organization, authorization systems and planning procedures, and healthy practices. The purpose of this study is to analyze the accounting system and internal inventory control and then make recommendations. The object of research at PT Sinar Sosro Sales representative office (KPP) Banjaran Bandung. This study aims to determine how the accounting system and internal inventory control are used. The method used in this research is to use descriptive analysis of secondary data, namely the research method carried out by collecting data for further research and drawing conclusions. shows the merchandise inventory accounting system is in accordance with the provisions of the procedure. This can be seen from the fulfillment of procedures in the inventory accounting system which includes related functions in the inventory accounting system. As the end of the research, the author submits suggestions to PT Sinar Sosro KPP Banjaran so that in an effort to obtain accurate and reliable information produced by the new inventory accounting system, the company needs to monitor data to check the completeness of the data for all reports.